2015
DOI: 10.1002/macp.201400599
|View full text |Cite
|
Sign up to set email alerts
|

A Novel (SiO2/MgO/MgCl2)·TiClx ZieglerNatta Catalyst for Ethylene and Ethylene/1‐Hexene Polymerization

Abstract: A novel (SiO 2 /MgO/MgCl 2 )·TiCl x Ziegler-Natta catalyst for ethylene and ethylene/1-hexene polymerization is successfully developed through impregnation of aqueous solution of watersoluble Mg-compounds such as magnesium acetate on silica gel, and forming a supported thin layer of magnesium oxide on the surface of SiO 2 after high temperature calcination in dry air or oxygen, followed by further reacting with titanium tetrachloride to synthesize the magnesium dichloride carrier in situ and to support the tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…[ 10 ] More recently, through the introduction of chromium species into this catalyst system, the catalytic properties were further improved. [ 24 ] Compared with these two catalysts, even better catalytic performance is expected for the novel vanadium-modifi ed (SiO 2 /MgO/MgCl 2 )·TiCl x ZN catalyst system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 ] More recently, through the introduction of chromium species into this catalyst system, the catalytic properties were further improved. [ 24 ] Compared with these two catalysts, even better catalytic performance is expected for the novel vanadium-modifi ed (SiO 2 /MgO/MgCl 2 )·TiCl x ZN catalyst system.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, TIBA was used as the cocatalyst because TIBA as the cocatalyst showed higher activity than TEA for the (SiO 2 /MgO/MgCl 2 )·TiCl x ZN catalyst as reported in our previous work. [ 10 ] The V-modifi ed ZN catalysts (MgV1:1/Ti, MgV5:1/Ti, and MgV10:1/Ti catalysts), Mg/Ti catalyst, and V/Ti catalyst were used in ethylene homopoly merization with different dosages of cocatalyst from 2.5 to 25 (Al/Ti molar ratio). Figure 1 showed the activities of the above catalysts.…”
Section: Ethylene Homopolymerization and Characterization Of The Polymentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, Wang et al successfully developed a novel (SiO 2 /MgO/MgCl 2 )·TiCl x Ziegler–Natta catalyst for ethylene and ethylene/1‐hexene polymerization showing high activity, good hydrogen response, and copolymerization ability. The method was simple and cost‐effective …”
Section: Introductionmentioning
confidence: 99%
“…The reactor was constructed such that it could be placed in a centrifuge, where precipitate and liquid phase could be separated efficiently. An amount of Our procedure for synthesizing the Ziegler-Natta PE catalyst followed a typical industrial procedure that can be found in patented literature [17], and it also resembles procedures described in other publications [18,19] and to some extent the recipe provided by Wang et al [20]. The carrier synthesis described by Nakayama et al [21] is an example of a support material preparation that resembles the recipe used in this study.…”
mentioning
confidence: 99%